Imaging Nano–Bio Interactions in the Kidney: Toward a Better Understanding of Nanoparticle Clearance - Wang, Junqing; Liu, Gang (Angewandte Chemie International Edition, 2018)
All clear! Highlighted is work aimed at a better understanding of nano–bio interactions for rational design of renal‐clearable nanoparticles in diseased kidneys. Renal clearance of ultra‐small gold nanoparticles (AuNPs) is not only dependent upon the Choi criteria but is also affected by the microphysiological structure of the glomerular barrier and the pathophysiological changes in the nephron.